1991
DOI: 10.1128/jb.173.2.801-809.1991
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mutations affecting the osmoregulated proU promoter of Escherichia coli and identification of 5' sequences required for high-level expression

Abstract: Expression of the Escherichia coli proU operon, which encodes an efficient uptake system for the osmoprotectant glycine betaine, is strongly increased in cells grown at high osmolarity. We isolated 182 independent spontaneous mutants with elevated expression of the chromosomal 4'lproV-lacZ) (Hyb2) fusion at low osmolarity. Genetic analysis demonstrated that eight of these mutant strains carried mutations closely linked to the fusion, whereas all others carried mutations that appeared to be in osmZ. All of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
55
0
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 52 publications
4
55
0
1
Order By: Relevance
“…The following lines of evidence indicate that binding of HNS to the NRE is associated with repression ofproU expression at low osmolarity. (i) proU expression is derepressed in hns mutants (6,17,23,24,31) and in cis mutants in which the NRE is deleted (6,24,29,31), whereas constructs lacking both HNS and the NRE are derepressed to the same extent as either of the single mutants (6,24,31). These experiments also demonstrated that P2R regulation is not significantly affected in hns mutants (6,24,31).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The following lines of evidence indicate that binding of HNS to the NRE is associated with repression ofproU expression at low osmolarity. (i) proU expression is derepressed in hns mutants (6,17,23,24,31) and in cis mutants in which the NRE is deleted (6,24,29,31), whereas constructs lacking both HNS and the NRE are derepressed to the same extent as either of the single mutants (6,24,31). These experiments also demonstrated that P2R regulation is not significantly affected in hns mutants (6,24,31).…”
supporting
confidence: 60%
“…One of the Lac' clones (designated GJ1003) was shown to have a mutation unlinked to proU that caused a two-to threefold derepression of proU::lac expression. The mutation was subsequently shown to be cotransducible with the trp locus at 27 min and also to confer a Bgl+ phenotype, properties characteristic of mutations in the hns (osmZ) locus (17,23). With the aid of a linked TnlO insertion (from CAG18455) (33), the hns mutation (designated hns-201) was transduced into GJ134, and the resultant strain was designated GJ1083.…”
mentioning
confidence: 99%
“…The results are somewhat complex to interpret, but the following conclusions may be drawn: (i) Plasmid pHYD275, carrying the region of proU from 376 to 552, does express the gene for P-galactosidase, and enzyme specific activity is increased sixfold at high osmolarity. Therefore, there is an osmotically regulated promoter (designated P1) in this segment, which is different from the one (designated P2) with the transcription start site at 628 characterized earlier (13,26,29).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to serving as part of the proV structural gene, the region implicated above in the negative control of proU expression carries a short open reading frame on the opposite (that is, bottom) DNA strand which could conceivably encode a 70-residue peptide (beginning with a GTG codon complementary to base positions 929 to 927 on the top strand and terminating at a TAA stretch complementary to bases 719 to 717 [13]); this putative peptide has five S(T)PXX stretches in its sequence, a motif that has earlier been described to be especially prevalent in DNA-binding proteins (43). We considered the possibility that this region of DNA encodes a repressor protein involved in osmotic regulation of proU expression, because such an explanation would also account for (i) the failure of earlier attempts to identify a regulatory gene unlinked to proU (6,26) and (ii) the observation that the presence of proU on a multicopy plasmid does not lead to titration effects on regulation of the operon (14,41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation